OVERVIEW OF KNOWLEDGE ABOUT FIRST AID FOR HYPOTHERMIA IN MOUNTAIN CLIMBERS IN MAKASSAR - S.Kep., Ns., M.Kep., aminullah (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Hypothermia is a medical condition that occurs when body temperature drops abnormally. This condition occurs because the body can no longer produce enough heat to compensate for the heat loss that occurs. According to data obtained from BASARNAS between 2015 and 2018, accidents during climbing are often caused by several factors, with hypothermia being the most dominant with a percentage of 47%. The purpose of this study was to determine the description of knowledge about first aid for hypothermia in mountain climbers in Makassar.This study is a descriptive study with a population and sample of 133 climbers, selected using purposive sampling techniques . The data collection instrument uses a questionnaire. The results of the study showed that the level of knowledge of climbers about First Aid for Hypothermia, the majority of whom had good knowledge, as many as 107 climbers (80.5%), and a small portion had sufficient knowledge, as many as 26 climbers (19.5%). The conclusion of this study is that the level of knowledge of mountain climbers in Makassar, especially in PKD South Sulawesi, about first aid for hypothermia is quite good. Several factors that can influence the results of the study include experience and information owned. It is expected that respondents can further improve their knowledge about first aid for hypothermia by seeking information from various sources, such as mass media and the internet, and attending training. Thus, it is expected to reduce the number of hypothermia cases that occur during climbing.